ADSORPTION OF Mg(II) ION FROM AQUEOUS SOLUTION ON CHITOSAN BEADS AND CHITOSAN POWDER - Sari Edi Cahyaningrum; N Narsito; Sri Juari Santoso; Rudiana Agustini (JOURNAL OF COASTAL DEVELOPMENT, 2010)
A basic investigation on the removal of Mg(II) ion from aqueous solution by chitosan beads was conducted in a batch adsorption system. The influence of different experimental parameters; pH, agitation period and different concentration of Mg(II) ion was evaluated. A pH 7.0 was found to be an optimum pH for Mg(II) adsorption onto chitosan powder and chitosan beads. The Langmuir and Freundlich adsorption isotherm models were applied to describe the isotherms and isotherm constants for the adsorption of Mg(II) onto chitosan powder and chitosan beads. Results indicated that Mg(II)  uptake could be described by the Langmuir adsorption model. The maximum adsorption capacities of Mg(II) ion onto chitosan powder and chitosan beads were 7.20 and 17.39 mol gâ^’1, respectively. The rate of adsorption Mg(II) on chitosan powder and chitosan beads  were 16.0.10-4 min-1 and  48.00 . 10-4  min-1, respectively.